Carbohydrate ingestion/supplementation for resistance exercise and training - Conley, M. S.; Stone, M. H. (Sports Medicine, 1996)
Aerobic endurance exercise has been shown to deplete muscle glycogen primarily in Type I muscle fibers. As the intensity of exercise increases, glycogen depletion from Type II fibers increases. Thus, it would seem reasonable to assume that carbohydrate (CHO) supplementation would enhance recovery from and possibly performance in anaerobic exercise. CHO ingestion following resistance exercise has been shown to enhance muscle glycogen resynthesis. CHO ingestion during or immediately following resistance exercise has been shown to increase postexercise insulin and growth hormone levels. Despite the postulation of potential benefits of CHO ingestion for resistance exercise performance there is little empirical evidence to support such a contention. Implication. CHO ingestion aids in recovery from resistance exercises but there is no substantial evidence that shows it improves performance or adaptation to that form of exercise stimulation.